Analisis Hidrologi dan Hidraulika pada Bangunan Pelimpah (Studi Kasus: Bangunan Pelimpah Bendungan Tugu) - Rizki, L.L. (Civil Engineering Department, Tadulako University, 2021)
Hydraulic design for spillway is a fundamental part of dam design. This research aims to conduct flow simulation at spillway of Tugu Dam using HEC-RAS program. Thus, simulation later is compared to Detailed Engineering Design. This simulation is carried out as the basis for analyzing the ability of the Tugu Dam spillway to flow the outflow discharge using the HEC-HMS program. The HEC-RAS simulation results show that the Tugu Dam spillway is able to drain DED outflow discharge but there is still runoff at the end of the channel. The HEC-HMS simulation provides the design flood discharge values for Q1000 and QPMF are 820 m3/s and 1161.2 m3/s, respectively. This result is higher than the DED design flood discharge of 670.95 m3/s for Q1000 and 928.44 m3/s for QPMF. Thus, changes were made to the spillway width to 45 m, the channel width to 40 m, and to raise the embankment +2 m in the lead channel and the end channel. The results of the flow simulation in the spillway with a modified design using HEC-RAS shows that there is no overtopping in the spillway. These indicate the spillway is able to flow the HEC-HMS design flood discharge properly.